2015
DOI: 10.1016/j.ultrasmedbio.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results on the Feasibility of Using ARFI/SWEI to Assess Cutaneous Sclerotic Diseases

Abstract: In this study, Acoustic Radiation Force Impulse (ARFI) and Shear Wave Elasticity Imaging (SWEI) were applied to the skin to investigate the feasibility of their use in assessing sclerotic skin diseases. Our motivation was to develop a non-invasive imaging technology with real-time feedback of sclerotic skin disease diagnosis. This paper shows representative results from an ongoing study recruiting subjects with and without sclerosis. The stiffness of the imaged site was evaluated using two metrics: mean ARFI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Normalized SWV was used by equation when comparing matched control sites. The equation was as follows: Cn=Cm·HcHs, where Cn was normalized mean SWV, Cm was measured mean SWV, Hc was the height of matched control healthy skin and Hs was the height of the sclerotic skin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normalized SWV was used by equation when comparing matched control sites. The equation was as follows: Cn=Cm·HcHs, where Cn was normalized mean SWV, Cm was measured mean SWV, Hc was the height of matched control healthy skin and Hs was the height of the sclerotic skin.…”
Section: Methodsmentioning
confidence: 99%
“…VTIQ has a smaller shear wave region of interest (SW‐ROI) (1 mm × 1 mm) than that of VTQ and may be suitable for skin tissue. Because of the advantage of shear wave elastography (SWE) in quantity, some research has reported that SWV could assess cutaneous sclerotic diseases including LS and SWV could differentiate sclerotic lesions from normal dermis . According to the recently clinical diagnostic criteria, the diagnosis and stage of LS is varied even by pathological results .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies verifying elastography as a method to examine skin pathologies involved primarily cancer patients [23][24][25][26][27] and individuals with chronic systemic inflammation [28][29][30][31][32][33][34][35][36]. Most of these studies confirmed that elastography is an accurate method to identify and quantify proliferative and fibrotic processes taking place in the skin.…”
Section: Application Of Elastography In Dermatologymentioning
confidence: 86%
“…The changes in ECM content during scaring make tissue stiffness amenable to being characterised with acoustic imaging, such as Acoustic Radiation Force Impulse (ARFI) and Shear Wave Elasticity Imaging (SWEI), to portray information regarding the stiffness of the target tissue . This advancement has allowed progressive tissue stiffness to be evaluated non‐invasively, serving as a valuable tool in the clinical understanding of progressive tension and maladaptive wound repair …”
Section: Mechanobiology Of Cutaneous Scarring and Mechanotherapymentioning
confidence: 99%